Diet-induced inflammation is associated with fatty pancreas in patients with common bile duct stones - Maedeh Chegini; Mohsen Shaygan Tabar; Vahideh Behrouz; Mohammad Bahrizadeh; Amir Sadeghi; Azita Hekmatdoost; Zahra Yari (Scientific Reports)
Abstract Inflammation has been proven to be associated with chronic diseases. We hypothesized that higher diet-induced inflammation is associated with increased risk of fatty pancreas (FP). Among 278 patients with common bile duct (CBD) stones, 89 patients were diagnosed with fatty pancreas (case group) during endoscopic ultrasonography and the other 189 patients were healthy in this regard (control group). Dietary inflammatory index (DII), empirical dietary inflammatory pattern (EDIP) and dietary inflammatory score (DIS) were calculated based on a 168-question valid food frequency questionnaire. Dietary inflammatory scores were significantly higher in the case group than in the control group. Based on logistic regression analysis, higher scores of DII, EDIP and DIS were significantly associated with higher risk of FP in the crude and adjusted models. In the full adjusted models, higher scores of DII (OR T2 vs T1 = 1.36; 95% CI 0.71–2.58 and OR T3 vs T1 = 3.3; 95% CI: 1.59–6.8; P for trend = 0.001), EDIP (OR T2 vs T1 = 1.7; 95% CI 0.89–3.3 and OR T3 vs T1 = 2.5; 95% CI 1.2–5.1; P for trend = 0.009) and DIS (OR T2 vs T1 = 1.48; 95% CI 0.74–2.97 and OR T3 vs T1 = 2; 95% CI 1.16–3.63; P for trend = 0.040) resulted in increased risk of FP development. Diet-induced inflammation was associated with an increased propensity for developing fatty pancreas.